(untitled) (New York, 2002)
Equips physicians with a practical guide to the diagnosis and treatment of the 20 most common GI problems encountered in day-to-day practice. The book takes a holistic approach to enhance patient participation, adherence, family dynamics, and satisfaction with care.
Keywords: Gastrointestinal system,Primary care (Medicine); Diseases